THE ERADICATION OF IUU FISHING IN INDONESIA FOR ECONOMIC FISHERIES - Agus Suherman; Mas A Santosa; Dian Wijayanto; Rahmadi Sunoko; Stephanie Juwana (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2020)
Illegal, Unreported and Unregulated (IUU) fishing poses a significant challenge to the management of marine and fisheries resources. This practice brings negative impacts on several aspects, including the economy. To address this problem, the Government of Indonesia established a special Task Force to Combat Illegal Fishing, which later is known as Task Force 115, through a Presidential Regulation Number 115 of 2015. Task Force 115 was formed with a mandate to execute law enforcement operations to combat illegal fishing. In general, the existence of Task Force 115 brings favourable impacts to the economy, especially from the fisheries sector. It should be noted that, because Task Force 115’s main tasks are enforcement related, the impacts to the economy are not direct. The purpose of this study was to analyse the role of the Task Force 115 in IUU fishing eradication activities that occur in the jurisdictional areas of the Republic of Indonesia in terms of the economic fisheries. Efforts of combating illegal fishing does not necessarily generate an increase in fisheries GDP, tax income and exports. Instead, those positive impacts are attributed to a set of policies imposed by the Ministry of Marine Affairs and Fisheries since 2014, which oriented to the responsible and sustainable fisheries. The establishment of Task Force 115 was part of that. Task Force 115’s works created deterrence and triggered compliance of fisheries business actors with the prevailing laws and regulations. Compliance eventually brings positive impacts on the economy. In 2015, growth of fisheries GDP, which amounted to 8,37%, surpassed national GDP of 4.79%. The growth of fisheries GDP reached its peak during the fourth quarterly of the year, which is 8,96% from last year’s during the same period. In 2016, the growth of fisheries GDP reached 5.15%.